Evaluation of the Implementation of Character Education in Adiwiyata Schools: A Case Study at SDN Cendono I and SDN Sumberejo I - Susanti, Enik; Harris, Taufiq; Wahyudi, M. Furqon; Rimadani , Eprilia (The Future of Education Journal, 2026)
This study aims to evaluate the implementation of character education in Adiwiyata schools through a case study at SDN Cendono I and SDN Sumberejo I, Pasuruan Regency. Character education has become a strategic national agenda in Indonesia to respond to moral degradation, the erosion of social solidarity, and the weakening of environmental awareness among elementary school students. Using a descriptive qualitative case study design, data were collected through in‑depth interviews with principals, teachers, and students, participant observation of school routines and Adiwiyata activities, and documentation analysis of school policies and supporting instruments. The data were analyzed using interactive techniques of data reduction, data display, and conclusion drawing with triangulation across sources and techniques to enhance validity. The findings show that character education has been integrated into school culture, classroom learning, and environmentally based co‑curricular programs, particularly in strengthening environmental care, discipline, and responsibility. Supporting factors include strong principal leadership, teacher commitment, active parental involvement, and the availability of Adiwiyata facilities, while inhibiting factors relate to limited resources, inconsistent student participation, and varying levels of community support. Overall, the implementation of character education in both Adiwiyata schools is categorized as effective, but still requires strengthening in systematic evaluation mechanisms, documentation of character outcomes, and collaboration with external stakeholders to ensure sustainability.​